2022
DOI: 10.3390/su14094891
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Matching Analysis and Development Strategies of County Night-Time Economy: A Case of Anning County, Yunnan Province

Abstract: The Chinese government regards the night-time economy as one of the essential means to expand domestic demand and enhance sustainable economic development. Scientifically choosing the night-time economic development path of the suburban counties of the Chinese metropolis (SCCM) and proposing a reasonable spatial matching planning strategy is an urgent problem for Chinese local governments. This study takes Anning county, a suburban Kunming metropolitan area, as the research area. Using Python to capture multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Wu et al researched the carbon-neutral energy consumption and emission volatility: the causality analysis of ASEAN region. They found that the green consumptions decrease the CO2 emissions in Asean countries [28][29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wu et al researched the carbon-neutral energy consumption and emission volatility: the causality analysis of ASEAN region. They found that the green consumptions decrease the CO2 emissions in Asean countries [28][29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The multiplier brought by consumption coupons in China during the 2020 epidemic is around 5-25, which has a significant effect on the GDP in the short term [22]. Consumption coupons are conducive to activating the frozen domestic demand [23] and market dynamics under the epidemic and make up for the short-term gap in overseas markets due to the global spread of the epidemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other country like China and Wales, the government has the policy to develop the night-time economy [17,21,22]. In Vietnam, the night-time economy has recently emerged and developed in various forms: pedestrian zones, shopping malls, food courts, convenience stores, night markets, bars, some art activities, and street entertainment.…”
Section: Introductionmentioning
confidence: 99%
“…The role for the economy shows that strong and vibrant development can bring many benefits in terms of growth, for a city or a country by attracting more. Workers and tourists come to use and enjoy variety goods and services provided by NTE [11,17,19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation